A context specific machine replacement model: a case study of forest harvesting equipment. Issue 3 (2nd September 2017) - Cantú, Ricardo Pedro; LeBel, Luc; Gautam, Shuva
ABSTRACT: There are a wide variety of machine replacement models available in the literature. However, we postulate that any model needs to be customized to account for the context in which machines are operated. The objective of this research was to adapt an existing machine replacement model for the case of forest harvesting contractors operating in remote areas, such as those found in Eastern Canada. First, a requirement analysis was conducted to identify the gap between published machine replacement models and managerial practices. Next, an existing model was customized to integrate the specific needs of harvesting contractors. More specifically, working capital, variable utilization, and a mix of capital and borrowed funds were factored into the model. The findings serve as a guideline for machine replacement and future research. The proposed model can serve as a valuable tool for practitioners to make optimal fixed asset management decisions.